Analysis of the Role of the National Land Agency (BPN) in Resolving Land Boundary Disputes in Rural Rembang Regency - putrianggraini1_24 (Faculty of Law, Universitas Negeri Semarang, 2025)
The problem of land disputes often arises and has become an unavoidable issue from time to time due to the growing human population while the number of land plots is limited. This encourages improvements in the arrangement of land parcels and land use, especially related to legal certainty for the community. In fact, for most rural communities, the settlement of land disputes is done through non-litigation channels because it is considered more effective and does not take much time. Article 1 point 10 of Law Number 30 of 1999 concerning Arbitration and Alternative Dispute Resolution regulates various alternatives to land dispute resolution through non-litigation channels. The role of the National Land Agency is very important in ensuring that the process of resolving land boundary disputes is carried out in accordance with legal provisions. The problems of this research are 1) What obstacles are faced by the National Land Agency (BPN) in resolving land boundary disputes. 2) The effectiveness of land boundary dispute settlement through mediation by the National Land Agency (BPN) in Rembang Regency. The research method used in this research is empirical juridical with a qualitative research approach and data collection techniques through interviews and documentation studies. The results of this study show that the effectiveness of land boundary dispute resolution through mediation by the BPN of Rembang Regency still faces various challenges that affect its success. Mediation often does not fully meet the principles of legal effectiveness, such as legal certainty, acceptance of the parties, efficiency of the process, and sustainability of the solution. Although mediation is considered a faster and cheaper method than litigation, its effectiveness still needs to be improved through systematic efforts to overcome obstacles in resolving land boundary disputes through mediation mechanisms. KEYWORDS Effectiveness, Role, BPN, Land Boundary Disputes